RC shear walls: Full-scale cyclic test, insights and derived analytical model. (1st November 2015) - Bekő, Adrián; Rosko, Peter; Wenzel, Helmut; Pegon, Pierre; Markovic, Damijan; Molina, Francisco Javier
Highlights: Novel cyclic testing was devised for full-scale low aspect ratio RC walls in shear. Hysteretic work diagrams, energy dissipation and damping ratios were assessed. Shear strength of the wall was evaluated using advanced analysis and code formulae. A nonlinear mathematical hysteresis model of the investigated walls is presented. Abstract: The unpredictable consequences of earthquakes have proven the necessity to study the shear mechanism of low-rise reinforced concrete walls further. Experimental testing remains the preferred approach to gather insight into the workings of the material and structural elements as the complex behavior of reinforced concrete does not lend itself to widely applicable generalized solutions. The contribution deals with cyclic testing of full-scale low aspect ratio reinforced concrete walls in a principally uniform shear state. An approach with various novel aspects in testing massive specimens is introduced. The obtained data was analyzed resulting in well-defined hysteresis curves. Characteristics of ultimate shear capacity, energy dissipation, damping and nonlinear effects are discussed. It was found that the sequence of load cycle amplitudes at the quasi-static rate does not significantly influence ultimate strength or overall behavior of the wall. Yet, hysteretic damping ratios depend on loading history and range from values considerably higher than commonly assumed in design to values that are lower. An advanced shear strength calculation is presented to relate the findings to previous research. A nonlinear mathematical model is described which is capable of simulating the hysteresis of the tested shear walls. The reported developments are applicable in design of structures.